ORGANIZATIONAL BARRIERS AND WORK LIFE CONFLICT AS POTENT SOURCES OF THE GLASS CEILING SYNDROME - SELVAKKUMAR, DR.MALATHI (International Journal of Advanced Science and Technology, 2019)
In today"s scenario Work life Conflict and glass ceiling is a major concern for the women who have opted to come out of their domestic chores and have chosen to work outside. Competition and challenges in the organization demand the time of women which they actually wanted to devote to their families. This imbalance can also create Glass ceiling preventing women from climbing hierarchical ladder. Review of literature on work life balance and glass ceiling of women employees has been carried out keeping in mind the objectives of the study. The researcher has reviewed the previous literature on various aspects related to work life balance (WLB). Review on Glass Ceiling is also focused in this paper. The main purpose of this paper is to find out the gap and the need to conduct this research